Ontological, Epistemological, and Axiological Dimensions in Wordsworth’s “Lucy” Poems: A Literary Analysis for Multidisciplinary Inquiry - Rai, Manju; Rai, Himal Ser (NPRC Journal of Multidisciplinary Research, 2025)
Background: William Wordsworth's "Lucy" poems are quintessential works of British Romanticism; as such, they have traditionally been examined within literary-critical frameworks that stress themes such as nature, love, and loss. However, these famously enigmatic lyrics provide a dense, under-explored site for philosophical investigation-one that engages directly with fundamental questions of being, knowledge, and value.Objectives: The paper will conduct a multidisciplinary literary analysis of "Strange Fits of Passion Have I Known" and "She Dwelt Among the Untrodden Ways" using an integrated philosophical framework centered on ontology, epistemology, and axiology. This should serve to illustrate in detail how both poems function as poetic thought experiments that go beyond mere thematic reading into investigating the construction of existence, the limits of understanding, and the bases of worth.Methods: The study uses a close-reading method based on literary analysis and philosophical hermeneutics, applying the basic tenets of ontology (the nature of being), epistemology (theories of knowledge), and axiology (the study of value) to the textual fabric of the poems. This is an approach that synthesizes literary theory with philosophical concepts to construct an interdisciplinary interpretation.Analysis: The ontological analysis discloses the ambiguous being of Lucy both as an essential, solitary entity and a relational construct of the lover's consciousness set within an ecological system. The epistemological search brings into focus the poems' validation of non-rational, affective, and intuitive ways of knowing over empirical or social knowledge in moments of emotional revelation. Axiological scrutiny discloses a core conflict between intrinsic, poetic value and extrinsic, social valuation, positioning Lucy as an emblem of worth derived from subjective difference rather than public recognition.Conclusion: The “Lucy” poems are sophisticated artistic engagements with perennial philosophical problems. They propose an ontology of modest and relational being, an epistemology privileging passion and intuition, and an axiology centered on intrinsic worth. This multidisciplinary reading affirms literature's capacity to explore abstract concepts through affective and aesthetic experience, offering a model for integrated knowledge that bridges disciplinary divides.Novelty: The paper offers a new, synthesized philosophical reading of Wordsworth's lyrics, uniquely applying the tripartite framework of ontology, epistemology, and axiology in concert. It positions the poems not merely as elegiac lyrics but as vital contributions to Romantic-era thought on the limits of reason, the ethics of attention, and the valuation of the marginal, with significant consequences for contemporary interdisciplinary humanities research.